Accelerated diversification and functional trait evolution in Velloziaceae reveal new insights into the origins of the campos rupestres’ exceptional floristic richness - Alcantara, Suzana; Ree, Richard H; Mello-Silva, Renato (Annals of botany, 2018)
Abstract Background and Aims The greater diversity of plant clades in the Neotropics compared to their relatives in Africa is a pervasive pattern in biogeography. To better understand the causes of this imbalance, we studied the diversification dynamics of the monocot family Velloziaceae. In addition to being conspicuously richer in the Neotropics compared to the Palaeotropics, many species of Velloziaceae exhibit extreme desiccation tolerance (i.e. ‘resurrection’ behaviour), and other ecological specializations to life on rocky outcrops, poor sandy soils, open vegetation and seasonally dry climates. Velloziaceae is also ecologically dominant in the campos rupestres, a habitat having exceptionally high plant diversity and endemism in Brazil. Methods We reconstructed a densely sampled time-calibrated molecular phylogeny and used state-dependent and state-independent models to estimate rates of lineage diversification in relation to continent-scale geographical occurrence and functional traits associated with desiccation tolerance and water storage capacity. Key Results Independent shifts to faster diversification occurred within two Neotropical lineages, Vellozia and Barbacenia. The Vellozia radiation was associated with the presence of conspicuous aerial stems, and was followed by decreasing diversification rates during the Oligocene, a time of rising global temperatures and expanding open areas around the world. The Barbacenia radiation was faster and more recent, occurring during the cooling conditions of the Miocene, and associated with the acquisition of aquiferous parenchyma on the leaves. Conclusions High species richness of Velloziaceae in South America has been driven by faster diversification in lineages predominantly occurring in the campos rupestres, putatively by the evolution of adaptive strategies in response to independent climatic events. The radiation of Vellozia in particular might have played a key role in the assembly of the campos rupestres vegetation.